Aspectos geomorfológicos del deslizamiento de Punta Colorada, Valle de Majes-Arequipa - Bedia Guillén, Ciro (2012)
The region of present forearc of the southern coast of Peru, has many structures of very recent tectonic activity, as they are active faults, current volcanic activity, large landslides and surveys of marine terraces; are landslides found in the foothills of the Pacific, as slipping Punta Colorada, which protrude into the classical topography so large scars, which can clearly distinguish the surface of starting, and the various components of the slip body, these are still active due to the activity current seismic sur-Peruvian forearc.